Lessons learned from the COVID-19 response in Sri Lankan hospitals: an interview of frontline healthcare professionals - Munasinghe, Nimali Lakmini; O'Reilly, Gerard; Cameron, Peter (Frontiers in Public Health, 2023)
The COVID-19 pandemic revealed the lack of preparedness in health systems, even in developed countries. Studies published on COVID-19 management experiences in developing countries, including Sri Lanka, are significantly low. Therefore, lessons learned from pandemic management would be immensely helpful in improving health systems for future disaster situations. This study aimed to identify enablers and barriers to COVID-19 management in Sri Lankan hospitals through healthcare workers' perceptions. Frontline doctors and nurses from different levels of public hospitals were interviewed online. Both inductive and deductive coding and thematic analysis were performed on the transcribed data. This study identified four themes under enablers: preparing for surge, teamwork, helping hands and less hospitalacquired infections. Seven themes were identified as barriers: lack of information sharing, lack of testing facilities, issues with emergency equipment, substandard donations, overwhelmed morgues, funding issues and psychological impact. These preparedness gaps were more prominent in smaller hospitals compared with larger hospitals. Recommendations were provided based on the identified gaps. The insights from this study will allow health administrators and policymakers to build upon their hospital's resources and capabilities. These findings may be used to provide sustainable solutions, strengthening the resilience of the local Sri Lankan health system as well as the health systems of other countries.